POS1177 TREATMENT WITH LORECIVIVINT LEADS TO IMPROVED LONG-TERM PATIENT ACCEPTABLE SYMPTOM STATE (PASS) COMPARED TO PLACEBO: DATA FROM PHASE 3 EXTENSION TRIAL - Swearingen, C.; Yazici, Y.; Tambiah, J. R. S.; Conaghan, P. G. (Annals of the rheumatic diseases, 2024)
Background:Lorecivivint (LOR), an intra-articular CLK/DYRK inhibitor thought to modulate inflammatory and Wnt pathways, has demonstrated beneficial effects on clinical and radiographic outcomes in early phase knee osteoarthritis (OA) clinical trials. While clinical outcomes focus on differences between treatment groups, an individual’s “acceptable symptom state” may provide a meaningful and clinically relevant assessment (Roos 2019). Year 1 results from a 2-year Phase 3 extension study, OA-07 (NCT04520607), which evaluated LOR 0.07 mg safety and efficacy with clinical outcomes including WOMAC Pain [0-100] and WOMAC Function [0-100] subscales, are reported here within the context of the Patient Acceptable Symptom State (PASS).Objectives:To evaluate long-term, repeated usage of LOR in patients with severe knee OA as assessed by PASS.Methods:Patients with structurally advanced knee OA (medial joint space width [JSW] 1.5-4.0 mm) who completed the parent Phase 3 trial (OA-11, NCT 03928184) were eligible for enrollment into the OA-07 trial. A repeat injection according to the parent trial randomization (LOR/ placebo (PBO) was given at the beginning of the OA-07 trial’s single-blind (patients and investigators) phase. PASS was assessed annually at start and at the end of OA-07 Year 1 (irrespective of symptom state) using a ‘yes/no’ response to the question “Taking into account all the activities you have during your daily life, your level of pain, and also your functional impairment, do you consider that your current state is satisfactory?” PASS response and odds ratios (OR; 95% CI) between treatment groups were calculated using baseline-adjusted logistic regression. Differences between treatment groups were explored for those patients with a positive PASS response.Results:276 patients (mean age 61.0 ± 8.2 years, BMI 31.8 ± 4.9 kg/m2, female 62.7%, KL3 45.3%, medial JSW 2.63 ± 0.69 mm, 67.4% bilaterally symptomatic, 68.5% medial JSW < 3 mm) were enrolled. LOR appeared safe and well-tolerated with no major adverse event rate differences compared to PBO during OA-07 Year 1. Treatment with LOR significantly increased the odds of reporting a ‘yes’ PASS response at the end of Year 1 (LOR 103 of 121 (85.1%) vs PBO 93 of 129 (71.1%), OR 2.45 [1.25, 4.78], P=0.009). Patients with a positive PASS response also reported greater improvement in WOMAC Pain (LOR -6.8 (± 2.0) vs PBO -1.0 (± 2.1), t-test P=0.049) and WOMAC Function (LOR -7.0 (± 1.9) vs PBO -2.4 (± 1.9), t-test P=0.090) at the end of Year 1 following the repeat injection at the start of the OA-07 extension study.Conclusion:In this analysis of a phase 3 extension study of LOR compared to PBO, patients treated with LOR were significantly more likely to achieve a patient acceptable symptom state 12 months after a second injection. Pain and function outcomes showed greater improvement for those subjects reporting an acceptable symptom state. These data suggest that multiple once-yearly doses of LOR are safe and may provide long-term benefits for knee OA symptoms.REFERENCES:[1] Roos EM, et al. Br J Sports Med 2019;53:1474-1478. doi:10.1136/bjsports-2018-100260Figure 1.Patient Acceptable Symptom State between LOR and PBO at End of Year 1 ExtensionAcknowledgements:NIL.Disclosure of Interests:Christopher Swearingen Biosplice Therapeutics, Yusuf Yazici Biosplice Therapeutics, Jeyanesh R S Tambiah Biosplice Therapeutics, Philip G. Conaghan AbbVie, Eli Lilly, Novartis, AbbVie, BMS, Eli Lilly, Galapagos, Genascence, GSK, Grunenthal, Janssen, Levicept, Moebius Medical, Novartis, Stryker, Takeda, TrialSpark